2006
DOI: 10.1128/aac.50.4.1376-1383.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacodynamics of a New Cephalosporin, PPI-0903 (TAK-599), Active against Methicillin-Resistant Staphylococcus aureus in Murine Thigh and Lung Infection Models: Identification of an In Vivo Pharmacokinetic-Pharmacodynamic Target

Abstract: PPI-0903 is a new cephalosporin with broad-spectrum activity, including beta-lactam-resistant Streptococcus pneumoniae and Staphylococcus aureus. We used the neutropenic murine thigh and lung infection models to examine the pharmacodynamic characteristics of PPI-0903. Serum drug levels following four fourfold-escalating single doses of PPI-0903 were measured by microbiologic assay. In vivo postantibiotic effects (PAEs) were determined after doses of 1.56, 6.25, 25, and 100 mg/kg of body weight in mice infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Findings for ceftaroline against S. aureus in a neutropenic-murine thigh infection model demonstrated that a median (min, max) f%TϾMIC of 26 (15,36) was associated with net bacterial stasis (10), an endpoint correlated with a high percentage of successful outcomes in patients with ABSSSI (2). Given the limited number of low f%TϾMIC values and the above-described uncertainty of the mathematical function in this region, it is difficult to evaluate the concordance of these data and precisely estimate the probability of microbiological response at a f%TϾMIC of 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings for ceftaroline against S. aureus in a neutropenic-murine thigh infection model demonstrated that a median (min, max) f%TϾMIC of 26 (15,36) was associated with net bacterial stasis (10), an endpoint correlated with a high percentage of successful outcomes in patients with ABSSSI (2). Given the limited number of low f%TϾMIC values and the above-described uncertainty of the mathematical function in this region, it is difficult to evaluate the concordance of these data and precisely estimate the probability of microbiological response at a f%TϾMIC of 26.…”
Section: Discussionmentioning
confidence: 99%
“…The PK-PD index of interest in this evaluation was the percentage of time the free-drug concentration remained above the MIC (f%TϾMIC), the measure that has been demonstrated to be most predictive of ceftaroline efficacy on the basis of nonclinical data (10). The estimation of f%TϾMIC values was based on the MICs for baseline pathogens and a previously developed population PK model (11).…”
mentioning
confidence: 99%
“…The best PK/PD index to predict the efficacy of ceftaroline is the percentage of the time for which the free serum concentration is above the MIC (fT >MIC ) [19]. The bacteriostatic effect of ceftaroline is achieved when unbound drug concentrations exceed the MIC for 30% of the dosing interval (fT >MIC > 30%) for Gram-negative bacilli.…”
Section: Organismmentioning
confidence: 99%
“…For S. pneumoniae, f %TϾMIC targets associated with these endpoints were 35, 44, and 51, respectively. These studies evaluated four S. aureus isolates (including one MRSA isolate) and five S. pneumoniae isolates (one penicillin susceptible, one with intermediate sensitivity, and three penicillin resistant) (9). Nonclinical PK-PD targets associated with net bacterial stasis and 90% animal survival have been shown to be correlated with a high percentage of successful outcomes in patients with ABSSSI and pneumonia, respectively (17).…”
Section: Methodsmentioning
confidence: 99%
“…For each dosing regimen and renal function group, the percentage of simulated patients achieving PK-PD targets was assessed by MIC value. PK-PD targets were based on f %TϾMIC, the PK-PD index associated with efficacy for ceftaroline (9). Specific f %TϾMIC targets associated with various levels of bacterial reduction from baseline for S. aureus and S. pneumoniae based on data from a neutropenic murine thigh infection model were assessed.…”
Section: Methodsmentioning
confidence: 99%